Rural School Libraries Anchoring Community Mental Health Literacy - Adkins, Denice; Brendler, Beth; Townsend, Kerry; Maras, Melissa (Qualitative and Quantitative Methods in Libraries, 2019)
Across the United States, one in five children has or will have a serious mental illness. This project intended 1) to determine current efforts among rural school libraries and communities to promote mental health literacy, and 2) to determine rural school libraries’ capacity to promote community health literacy. This project used a mixed method design, including activities such as a quantitative survey of mental health support administered to rural school librarians, counselors, and administrators; qualitative interviews and focus groups with rural school librarians, counselors, and administrators; environmental analyses of school libraries where best practices are happening.